STUDI KOMPARASI PRESTASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN MATEMATIKA YANG SANGAT GEMAR, KADANG-KADANG DAN TIDAK GEMAR BERMAIN GAME ONLINE DI KELAS V SDN 15 SEMPALAI KECAMATAN TEBAS TAHUN PELAJARAN 2019/2020 - Nazrin Nazrin; Eliyah Eliyah; Arnadi Arnadi (Jurnal Salome : Multidisipliner Keilmuan, 2023)
This study aims to reveal the significant differences between student achievement in mathematics subjects who like, sometimes and do not like playing online games in class V SDN 15 Sempalai, Tebas District, 2019/2020 academic year. This study uses a mixed approach or Mix Method. The type of research used is Sequential Exploratory Design. The number of research samples totaling 44 people is the whole of the research population, so this research is called population research or saturated population. Data collection techniques using interviews, and documentation. The qualitative data analysis technique used is the Miles and Huberman model, while the quantitative data analysis technique uses the One Sample t test and One Way Anova analysis. The results showed that; There is no significant difference between the learning achievement of students in the group who really likes, sometimes and does not like to play online games, seen from the value of learning achievement in Mathematics for Class V at SDN Sempalai. This is evidenced by the value of Sig. One Way Anova analysis of 0.298 > from 0.05; it means that Ho is accepted and Ha is accepted, that is, there is no significant difference between mathematics learning achievement of fifth grade students at SDN 15 Sempalai. With the average of each group: The group who really likes to play online games: 46%; Group that occasionally plays online games: 45%; and Groups who do not like to play online games: 51.21%